Transformation of the Perak Api Ritual: Negotiating Between Sasak Tradition, Islam, and Global Modernity - Abdurrazak Abdurrazak; Noorhaidi Hasan; Moh Soehadha (An-Nida', 2026)
The transformation of local traditions within Muslim societies frequently engenders tensions among traditional cosmology, Islamic values, and modern rationality. This phenomenon is exemplified by the Perak Api ritual, a component of the birth traditions of the Sasak community in Lombok, which is believed to serve as a protective mechanism for postpartum mothers and newborn infants. The present study seeks to describe the practice of the Perak Api ritual and to analyse its transformation within the contexts of Islamisation and global modernity. This research is significant as it illustrates how local communities maintain their cultural identity through processes of symbolic adaptation, without wholly relinquishing their ancestral traditions. Employing a qualitative-descriptive methodology with a phenomenological approach, data were collected via observation, in-depth interviews, and documentation in East Praya District, Central Lombok. Participants included religious leaders, traditional leaders, belian nganak (traditional birth attendants), and members of the Sasak community. The findings indicate that the Perak Api ritual is conducted through three principal stages—separation, liminality, and incorporation—each embodying symbols of protection, purification, and the restoration of socio-cosmological balance. Furthermore, the study identifies the concept of “Perak Api Lebur Anyong” as a form of transformation from local cosmology towards cultural Islamisation and global modernity, achieved through processes of symbolic negotiation. The contribution of this study lies in advancing the discourse on lived Islam and the cultural transformation of local Muslim communities amid contemporary social change.